If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 3b + -2b Combine like terms: 3b + -2b = 1b 9 = 1b Solving 9 = 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 9 + -1b = 1b + -1b Combine like terms: 1b + -1b = 0 9 + -1b = 0 Add '-9' to each side of the equation. 9 + -9 + -1b = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1b = 0 + -9 -1b = 0 + -9 Combine like terms: 0 + -9 = -9 -1b = -9 Divide each side by '-1'. b = 9 Simplifying b = 9
| 2+3x-6=x+20 | | 4a=27 | | 3x^2-5x=6x^2-6x-12x+2 | | 4x+8+3x-27=0 | | 2x-3=-10 | | 4(x-3)+7=35 | | 5-x=1+x | | 5x=1+x | | 9x^2-36x-8=0 | | 5x+5=54+2x | | X-5-=26 | | y-2=-1.5(x-(-2)) | | 12x-27=8x+21 | | 85+(4x-6)=x+1 | | (-4)+-1(-2)=m | | 13-10x=35-17x | | 10-7x=90x-21 | | n+38=51 | | 86-4x=8-8x | | y-2=2.2(x-(-2)) | | 6x+5=85-4 | | 11x-10=9x+4whatisx | | 4x+9=-33-7x | | 12-9x=135-30x | | 5(3a+4b)=15a+20b | | 9n-11=52 | | 4x-7-3x=9-3x+32 | | x(x+2)+1=144 | | b-3=1 | | 4x+6=69-7x | | -3c+4d+8c-5d= | | 3m-5m-4n+7n= |